Implementasi Pendidikan Karakter Islami melalui Program Kegiatan Sekolah Berbasis Masjid SDIT Cahaya Robbani Kabupaten Kepahiang - M. Andy Hermansyah (Scidac Plus, 2024)
This study aims to analyze the implementation of Islamic character education through mosque-based school activities programs at SDIT Cahaya Robbani in Kepahiang Regency. A qualitative approach with a case study method was used in this research. Data were collected through in-depth interviews, participatory observations, and related document analysis. The results showed that this program effectively improves students' discipline, responsibility, religiosity, religious understanding, empathy, and social awareness. Challenges faced include the lack of parental participation and inadequate mosque facilities. This study recommends enhancing cooperation with parents and improving mosque facilities to support the program's success. Thus, the mosque-based school activity program can serve as an effective model for Islamic character education in other schools.